2018
DOI: 10.1016/j.jad.2017.09.027
|View full text |Cite
|
Sign up to set email alerts
|

Screening for attention-deficit/hyperactivity disorder in borderline personality disorder

Abstract: We found a high prevalence of ADHD using structured interviews. The ASRS-v1.1 was not a sensitive screener for identifying possible ADHD cases in a BPD population, with a high number of false positives. When combined with the WURS-25, it offered improved screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 56 publications
2
14
0
Order By: Relevance
“…On the contrary, the rate of false positives was lower with a threshold of 4 (7.9-30.0%). This result is in line with other studies reporting a reduced sensitivity for screening tools when comorbid disorders are present (Kok et al, 2015;Luderer et al, 2019;Weibel et al, 2018) or the need of higher thresholds for screening tools used in population having comorbid disorders (Delgadillo et al, 2011).…”
Section: Main Findingssupporting
confidence: 92%
“…On the contrary, the rate of false positives was lower with a threshold of 4 (7.9-30.0%). This result is in line with other studies reporting a reduced sensitivity for screening tools when comorbid disorders are present (Kok et al, 2015;Luderer et al, 2019;Weibel et al, 2018) or the need of higher thresholds for screening tools used in population having comorbid disorders (Delgadillo et al, 2011).…”
Section: Main Findingssupporting
confidence: 92%
“…Because of this, it is crucial that clinicians systematically inquire about the potential comorbidity. However, despite the importance of screening for ADHD in the context of BPD (and vice-versa), screening tools lack the ability to discriminate ADHD in BPD patients31 and to our knowledge, the psychometric properties of BPD screening measures in adult ADHD have yet to be investigated. Therefore, clinicians should not rely on screening measures alone to make a diagnosis; instead, clinicians working in each field (BPD and ADHD) should be knowledgeable of the other field in order to effectively detect comorbid cases in clinical practice, based on the careful intake of the patient’s psychiatric and developmental history.…”
Section: Discussionmentioning
confidence: 99%
“…These results led the authors to conclude that their self-report scale was valid, as it assessed symptoms specifically found in ADHD. In two more recent studies however, Edebol et al37 and Weibel et al31 assessed the psychometric properties of the World Health Organization Adult ADHD Self-Report Scale v1.1 (ASRS-v1.1) and found that it lacked clinical specificity in adult ADHD (i.e., its ability to discriminate BPD alone from BPD+ADHD), a finding that was likely due to shared symptoms of emotion dysregulation and impulsivity 31. In addition, inattention may also be experienced in BPD, albeit in a special form as part of dissociative states, hence diminishing its power to discriminate the two disorders at least through self-report scales32…”
Section: Psychopathological Neuropsychological and Brain Mechanismsmentioning
confidence: 95%
“…In the current study, we used the 25 items of the WURS, which were found to best differentiate ADHD patients from healthy controls (Ward et al, 1993). This version of the WURS is commonly used in research (e.g., Barbaresi, Weaver, Voigt, Killian, & Katusic, 2018; Weibel et al, 2018).…”
Section: Methodsmentioning
confidence: 99%